3LRM-3 Layer Risk Mitigation Modelling of ICT Software Development Projects - Salma Firdose; L. Manjunath Rao (Institute of Advanced Engineering and Science, 2016)
With the adoption of new technology and quality standards, the software development firms are still encountering the critical issues of risk modelling. With the changing dynamics of customer needs, potential competition has being mushrooming in the global IT markets to relay a new standard of software engineering which has higher capability of sustaining risk. However, till date, it is still theoretical to large extent from research viewpoint. Hence, this paper presents a mathematical model called as 3LRM that is designed with the simple approach keeping in mind the real-time issues of risk factors in software engineering for ICT software development project. The study has also identified requirement volatility as one of the prominent source of risk and hence, the framework intends to identify a risk as well as mitigating the risk to a large extent. The paper is illustrated with some of the simple statistical approaches of random probability.